The disrupted sociologies of young people with harmful sexual behaviours. Issue 2 (4th May 2019) - Balfe, Myles; Hackett, Simon; Masson, Helen; Phillips, Josephine
ABSTRACT: Few studies, particularly few qualitative studies, have focused on the family and social contexts of young people with harmful sexual behaviours. This article, therefore, seeks to provide insight into the more detailed, lived experience of this group of young people. The article involved a thematic analysis of 117 cases, identified from nine services that work with children with sexual behaviour problems. While a number of young people were from stable backgrounds, others were from highly disrupted sociological situations characterised by chaotic families, erratic living situations, poor family relationships, unstable parental backgrounds, generalised neglect and abuse, sexual abuse and school/social problems. Many of these young people's lives appear to be characterised by varying degrees of liminality and chaos. Such chaos may not only be traumatic, it may potentially be traumagenic, and contribute to the emergence of sexual behaviour problems in some young people.